GENDER REPRESENTATION IN THREE ENGLISH TEXTBOOKS FOR ELEMENTARY SCHOOL STUDENTS:A Critical Pedagogy of Three English Textbooks of Elementary School - Mira Rahmani, - (2009)
The present study, which is entitled Gender Representation in Three English Textbooks for Elementary School Students (A Critical Pedagogy of Three English Textbooks of Elementary School), investigated how gender is represented in three English textbooks for Elementary School Students and attempts to explain such representation from the point of view of Critical Pedagogy. The data were obtained from three English textbooks written by the same authors and published by the same publisher. The qualitative approach was used to describe gender representation in the textbooks. Transitivity analysis using Hallidayan's Systemic Functional Grammar and Freire's theories of Critical Pedagogy were used as the tools of analysis. The results of data analysis suggested two important findings: (1) the three textbooks portrayed and represented males and females in a different and unequal way in terms of frequency of appearance and roles of participants in the texts, and (2) such gender representation was seen as something ideological that was in contrast to many principles in Critical Pedagogy, one of which was related to equality in education.